Sanitasi untuk Semua dalam Pendampingan Pengelolaan Sanitasi dan Penyediaan Air Bersih untuk Masyarakat Desa Tebing Tinggi - Zulkifli, Zulfan Fachrezi; Hendriyulianti, Dila Aprillia; Rahma, Fauzia; Ayu, Rima Mustika; Wicaksana, Bagas Putra; Pratama, Dwi Andika; Oktavinulia, Tri; Rosliani, Endah; Lestari, Raudho; Angelita, Heldy Basa (Studium: Jurnal Pengabdian Kepada Masyarakat, 2024)
Water is a fundamental component of human life, and adequate access to clean drinking water and proper sanitation is key to improving public health. In Indonesia, rapid population growth has led to an increasing demand for drinking water, hence the Community-Based Drinking Water and Sanitation Provision Program (PAMSIMAS) was implemented as an effort to overcome the problem of water availability in rural areas. Tebing Tinggi Village, Jambi Province, is one of the areas that experiences serious challenges related to water and sanitation. The Batanghari River, as the main source of life in this village, is often polluted due to irresponsible human behavior. This threatens water quality and the health of the local community. The people of Tebing Tinggi Village also experience difficulties in accessing clean water and some still rely on the river which is no longer suitable as a sanitation facility. To overcome these problems, assistance and counseling programs are needed. The Village Community Service Program (P2MD) involves students and the local government to empower the community in sanitation management and clean water provision. The aim of this program is to increase community knowledge and understanding of proper sanitation and have a positive impact on their health and well-being. With strong cooperation between the local government, students, and the community, this program is expected to provide sustainable solutions to water and sanitation problems in Tebing Tinggi Village, and contribute to the achievement of national development goals related to clean water and sanitation.